Assessment of the effect of grain refinement on the solidification characteristics of Al-Si-Cu eutectic cast alloy using thermal analysis technical (CA-CCTA) - M El-Aswad, Ashraf Mahmood (2015)
Aluminium (Al-Si-Cu) alloys are widely used in automotive, aerospace, and general engineering industries due to their excellent combination of properties, such as good castability, low coefficient of thermal expansion, and high strength-to-weight ratio. Recently, sustainability and recycling of resources are of paramount importance with increasing public awareness on environmental issues and energy, and depleting natural resources. In the case of Al-11.7 Si-Cu- alloys, this would involve the fineness of the primary α-Al dendrites (as determined by (SDAS) value), the Al-Si eutectic structure (Si morphology), as well as the CuAl2 and other copper intermetallic, depending upon the alloying and the trace elements present in the alloy. In addition, there has been no clear explanation of the present form of TiB5 additions via experimental observation on Al-Si-Cu- eutectic cast alloy. The objective of this research are to obtain the probable refiner concentrations of TiB5 additions in the base alloys and to evaluate the effects of these additions on solidification, microstructure and mechanical properties,. Moreover, the main objective of this research is to evaluate the the grain refinement treatments with the additions of (1.6-9.7) wt.% of TiB5, using Cooling Curve Thermal Analysis. Furthermore, the study also investigated the roles of TiB5 on microstructural constituents and formation of intermetallic, Furthermore, the study focuses on the effects of variable amount level of TiB5on mechanical properties, and microstructural. The results obtained were correlated with the earlier microstructural characterization, and thermal analysis. The additives investigated here were TiB5 (1.6-9.7) wt. % . Good agreement was observed between the results obtained for CA-CCTA, Si structure morphology, and SDAS. The microstructure shows that the smaller and the refiner structure of Si particles with 4.8 wt.% TiB5 additions reduced the size by 67-70% . The mechanical properties, such as hardness and impact toughness of base alloy, were improved with the additions of TiB5 by not more than 4.8 wt.%., where by lower strength and impact toughness were observed due to the intermetallic accompaniment with pore porosity defects, which increased by 6.8% with the increased level of additions. On the other hand, the value of hardness for Al-Si-Cu increased by 7-8% with the increase of TiB5 additions.